Influence of webinar based learning on practice of percutaneous nephrolithotomy: Outcomes of a global survey - TANIDIR, YILÖREN (My University, 2021)
Background With webinars looking to be the mainstay post-pandemic, it is important to demonstrate if webinars are indeed effective educational tools for professional training and skill acquisition. We aim to demonstrate, via a global survey, the efficacy of webinars on PCNL and how this knowledge transforms clinical practice. Methods A structured online survey covering the following sections: (1) Demographics, (2) PCNL techniques, (3) PCNL equipment, was circulated. The target study population were practicing urologists and residents. Categorical data were presented with counts and percentages, and compared using Chi-square test. Continuous data was analysed with non-parametric methods. Respondents were dichotomised according to attendance of webinars type, attendees of dedicated PCNL webinars (Group A) or attendees of endourological webinars that discussed some aspects of PCNL (Group B). Results A total of 303 respondents participated from 38 countries. 91.7% (n=278) were in Group A with 8.3% (n=25) in Group B. 77.9% were under the age of fifty years while 51.8% had more than 10 years of urology experience. In group A, urologists of all ages, in academic institutions and private practitioners, significantly benefitted in gaining knowledge about the merits of newer devices and the role of suction assisted devices in modern PCNL; Majority of group A also reflected that by attending a dedicated PCNL based webinar they benefited in learning newer positions for PCNL access, especially supine, and how to effectively use laser as energy devices for lithotripsy. In Group B, the only area of benefit was in lasing techniques and the use of newer lasers like the TFL. Conclusion Our survey positively validates the two proposed hypothesis i.e. webinars as a medium of education do benefit practicing urologists in knowledge and the clinical practice domains. Age, experience or place of practice is no barrier to adopting newer mediums of education like webinars.